Flame-retardant high-strength and tough modified nanocellulose and preparation method thereof, flame-retardant and tough balanced polyolefin
By grafting a hydrophobic agent on the surface of the nanocellulose and reacting with diisocyanate and diallyl ether compounds, modified nanocellulose with good hydrophobic, flame retardant and interface compatibility are prepared, and the nanocellulose and matrix are solved The problem of poor material compatibility significantly improves the mechanical and flame retardant properties of composite materials.
Patent Information
- Application Number
- CN202310562513.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-05-18
Smart Images

Figure BDA0004235522950000141 
Figure BDA0004235522950000142 
Figure BDA0004235522950000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material modification, and in particular to flame-retardant high-strength and tough modified nanocellulose and a preparation method thereof, and flame-retardant and strong-tough balanced polyolefin. Background Art
[0002] Nanocellulose can be simply divided into the following categories: (1) Cellulose nanocrystals (CNC). CNC is crystalline and usually whisker-like or spherical. Cellulose nanocrystals are also often called nanocrystalline cellulose (NCC), cellulose nanowhisker (CNW), etc. (2) Cellulose nanofibers (CNF). CNF has crystalline and amorphous regions, a large aspect ratio, and good flexibility. Cellulose nanofibers are also often called nanofibrillated cellulose (NFC), microfibrillated cellulose (MFC), etc. (3) Bacterial nanocellulose (BNC). BNC is a three-dimensional nano-network composed of microfibrils entangled with each other. It has high purity, a crystallinity of more than 95%, a high degree of polymerization, and good biocompatibility. When nanocellulose is used as a filler in polymer materials to prepare composite materials, it is very easy to agglomerate when mixed with matrix materials because of its rich hydroxyl groups on the surface, large specific surface area, and strong polarity, resulting in uneven dispersion, poor compatibility, and poor thermal stability in the matrix, thereby affecting the mechanical properties and flame retardant properties of the composite materials. Therefore, how to improve the compatibility of nanocellulose with the matrix material is a technical problem to be solved by the present invention.
[0003] In the document "Effect of surface modified CNF on the crystallization and mechanical properties of PLA / TPU blends", after CNF was modified with KH550, the dispersibility and compatibility of CNF-KH550 filler in the matrix were enhanced, but the phase separation between PLA and PBS and TPU polymers was still obvious. In patent CN 115433442 A "Biodegradable strong composite material and its preparation method", polylactic acid was first chain extended, and tannic acid and octadecylamine were grafted on the surface of cellulose nanocrystals for hydrophobic modification, which improved the compatibility of nanocrystals with polylactic acid and PBAT, thereby improving the mechanical properties of the composite material. In patent CN115636986 A "A nanocellulose composite filler and its preparation method and application", nanocellulose is first hydrophobically modified with a silane coupling agent, then coated with polypropylene glycol (PPG), and finally blended with PLA and PBAT materials to prepare a film. Its tensile strength is 12.1% higher than that of PLA / PBAT film, and its elongation at break is increased by 21.76%. Its performance improvement is not obvious, mainly because polypropylene glycol (PPG) is a polar substance and has poor interfacial compatibility with the hydrophobically modified nanocellulose. Summary of the invention
[0004] In order to solve the technical problem of poor compatibility between nanocellulose and matrix materials, the present invention provides flame-retardant, high-strength and tough modified nanocellulose and a preparation method thereof, and flame-retardant, strong-tough and balanced polyolefin. The present invention first grafts a hydrophobic agent on the surface of nanocellulose to make the nanocellulose obtain hydrophobic properties, and at the same time, under the action of diisocyanate, connects the nanocellulose with a hydroxyl-containing diallyl ether compound to obtain a modified nanocellulose with hydrophobic, flame-retardant and good interface compatibility. Since the graft has a diallyl ether compound, an amide group and an ester group, the double bond can be melt-reactively blended with polyolefins under the action of an initiator, and a copolymer is grafted in situ to enhance the interface compatibility between nanocellulose and polyolefins. Its flexible chain, amide group and ester group can improve the mechanical properties, heat resistance and toughness of the matrix material. In addition, it has hydrophobic and flame-retardant properties.
[0005] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0006] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0007] (1) grafting a hydrophobic agent onto the surface of nanocellulose to obtain hydrophobic nanocellulose, wherein the hydrophobic agent is a silane having at least one amino functional group;
[0008] (2) The hydrophobic nanocellulose and the hydroxyl-containing diallyl ether compound are subjected to a heating reaction under the action of diisocyanate to obtain flame-retardant and high-strength modified nanocellulose.
[0009] Furthermore, the nanocellulose includes one or more of cellulose nanocrystals, cellulose microcrystals, cellulose nanofibers, and bacterial nanocellulose.
[0010] The silane having at least one amino functional group is selected from one or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane;
[0011] The hydroxyl-containing diallyl ether compound is glycerol-Α,Α'-diallyl ether and / or 2,2-bis(allyloxymethyl)-1-butanol;
[0012] The diisocyanate is selected from one or more of hexamethylene diisocyanate (HDI), diphenylmethane diisocyanate (MDI), 2,2,4-trimethylhexane diisocyanate (TMDI), toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), and 4,4'-dicyclohexylmethane diisocyanate (HMDI).
[0013] Furthermore, the mass ratio of the hydrophobic nanocellulose, the hydroxyl-containing diallyl ether compound, and the diisocyanate is 1:(1.1-1.25):(0.85-0.95).
[0014] Furthermore, the temperature of the heating reaction in step (2) is 140-145° C., and the reaction is continued for 2-4 hours after the diisocyanate is added dropwise; wherein the diisocyanate needs to be added dropwise.
[0015] Furthermore, in step (1), the process of grafting the hydrophobic agent on the surface of the nanocellulose is: hydrolyzing the hydrophobic agent under alkaline conditions to obtain a hydrolyzate, adding the hydrolyzate to an ethanol dispersion of nanocellulose to carry out a grafting reaction at 50-75° C. for 24-32 hours, cooling, washing with alcohol and water for multiple times, and then drying to obtain the hydrophobic nanocellulose.
[0016] Furthermore, the mass concentration of the hydrophobic agent in the hydrolyzate is 3-5%, the pH of the alkaline condition is 8-10; the mass concentration of nanocellulose in the nanocellulose ethanol dispersion is 5-10%; and the mass ratio of the nanocellulose to the hydrophobic agent is 1:(1-5).
[0017] Another aspect of the present invention provides flame-retardant and high-strength modified nanocellulose obtained by the above preparation method.
[0018] The last aspect of the present invention provides a flame retardant and strong balanced polyolefin, which comprises the following components in parts by weight: 90-100 parts of polyolefin, at least 1 part of the flame retardant and high-strength modified nanocellulose obtained according to the above preparation method, and 0.2-0.4 parts of an organic peroxide initiator.
[0019] Preferably, the flame retardant, strong and tough balanced polyolefin comprises the following components in parts by weight: 90-100 parts of polyolefin, at least 10 parts of the flame retardant, high-strength and tough modified nanocellulose obtained according to the above preparation method, and 0.2-0.4 parts of an organic peroxide initiator.
[0020] Further, the polyolefin is one or more of PE, PP, PB, TPX, and thermoplastic elastomer; the organic peroxide initiator includes one or more of BPO, DCP, TMCH, DHBP, BIPB (odorless DCP), TBPB, TBCP, DBPH, DTBP, and double two five;
[0021] It also includes at least 0.1 parts of other processing aids, including but not limited to one or more of plasticizers, toughening agents, lubricants, antioxidants, antistatic agents, and auxiliary flame retardants, which can be selectively added according to actual needs and the usual functions in the art.
[0022] Furthermore, the preparation method of the flame-retardant, strong-tough and balanced polyolefin comprises the following steps: according to the formula, other materials except the organic peroxide initiator are melt-reactively blended at at least 150°C until torque balance is achieved, then the organic peroxide initiator is added and melt-reactively blended until torque balance is achieved, and the flame-retardant, strong-tough and balanced polyolefin is obtained after granulation.
[0023] Beneficial technical effects:
[0024] (1) The present invention uses silane with at least one amino functional group to graft the surface of nanocellulose, so that the nanocellulose has hydrophobic properties and terminal amino reactive groups; then, under the action of diisocyanate, one end is connected to the terminal amino group of the hydrophobic nanocellulose, and the other end is reacted with the side hydroxyl group of the hydroxyl-containing diallyl ether compound to obtain flame-retardant and high-strength modified nanocellulose;
[0025] Nanocellulose is conducive to carbonization, and its molecular structure contains siloxane, amide group, ester group and ether, forming an organic-inorganic hybrid siloxane-containing N-type flame retardant; when used in polyolefins, it can help the material release a large amount of non-combustible gases (such as carbon dioxide, nitrogen, water, etc.) during combustion. These gases can cause insufficient oxygen supply during the combustion process, effectively blocking heat transfer, oxygen and other combustible gases, and greatly improving the limiting oxygen index. The combustion grade reaches the V-0 level of the UL 94 standard; in addition, the flame-retardant high-strength and tough modified nanocellulose has a significant effect on improving the strength and toughness of the material;
[0026] (2) The flame-retardant, high-strength and tough modified nanocellulose of the present invention is melt-reactively blended with polyolefins under the action of an initiator, and in-situ grafted to form a copolymer, which can increase its interfacial compatibility with polyolefin materials and is beneficial to improving the strength, toughness, flame retardancy and heat resistance of the composite material. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0029] The experimental methods in the following examples without specifying specific conditions are usually measured according to national standards; if there is no corresponding national standard, it is carried out according to the general international standards or the standard requirements proposed by relevant enterprises. Unless otherwise specified, all parts are by weight and all percentages are by weight.
[0030] The following nanocellulose uses CNC.
[0031] Example 1
[0032] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0033] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0034] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0035] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 50° C. for 32 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 18 hours to obtain hydrophobic CNC;
[0036] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 140°C, start stirring, and add hexamethylene diisocyanate (HDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 2 hours. After the reaction is completed, flame-retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and HDI is 1:1.1:0.85.
[0037] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 90 parts of PP, 10 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 180°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0038] Example 2
[0039] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0040] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0041] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0042] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 60° C. for 24 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 18 hours to obtain hydrophobic CNC;
[0043] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 145°C, start stirring, add diphenylmethane diisocyanate (MDI) dropwise for heating reaction, continue the reaction for 3 hours after the addition is complete, and the reaction is completed to obtain flame-retardant and high-strength modified CNC; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and MDI is 1:1.1:0.85.
[0044] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 90 parts of PP, 10 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 190°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0045] Example 3
[0046] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0047] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0048] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0049] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 75° C. for 28 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 12 hours to obtain hydrophobic CNC;
[0050] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 145°C, start stirring, and add 2,2,4-trimethylhexamethylene diisocyanate (TMDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 4 hours. After the reaction is completed, flame retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and TMDI is 1:1.1:0.85.
[0051] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 90 parts of PP, 10 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and the flame retardant, high-strength and tough modified CNC are mixed in a mixer at 200°C and 50 rpm to achieve torque balance, and then DCP is added and mixed to achieve torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0052] Example 4
[0053] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0054] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0055] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0056] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 75° C. for 28 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 12 hours to obtain hydrophobic CNC;
[0057] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 145°C, start stirring, and add toluene diisocyanate (TDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 4 hours. After the reaction is completed, flame-retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and TDI is 1:1.1:0.85.
[0058] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 90 parts of PP, 10 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and the flame retardant, high-strength and tough modified CNC are mixed in a mixer at 200°C and 50 rpm to achieve torque balance, and then DCP is added and mixed to achieve torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0059] Example 5
[0060] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0061] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0062] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0063] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 50° C. for 32 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 12 hours to obtain hydrophobic CNC;
[0064] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 145°C, start stirring, and add isophorone diisocyanate (IPDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 2 hours. After the reaction is completed, flame-retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and IPDI is 1:1.1:0.85.
[0065] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 90 parts of PP, 10 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 180°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0066] Example 6
[0067] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0068] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0069] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0070] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 60° C. for 24 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 12 hours to obtain hydrophobic CNC;
[0071] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 145°C, start stirring, and add 4,4'-dicyclohexylmethane diisocyanate (HMDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 3 hours. After the reaction is completed, flame-retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and HMDI is 1:1.1:0.85.
[0072] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 90 parts of PP, 10 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 190°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0073] Example 7
[0074] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0075] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0076] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0077] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 60° C. for 24 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 24 hours to obtain hydrophobic CNC;
[0078] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 145°C, start stirring, and add hexamethylene diisocyanate (HDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 3 hours. After the reaction is completed, flame-retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and HDI is 1:1.25:0.95.
[0079] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 90 parts of PP, 10 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 190°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0080] Example 8
[0081] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0082] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0083] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0084] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 75° C. for 28 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 12 hours to obtain hydrophobic CNC;
[0085] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 140°C, start stirring, add diphenylmethane diisocyanate (MDI) dropwise for heating reaction, continue the reaction for 4 hours after the addition is complete, and the reaction is completed to obtain flame-retardant and high-strength modified CNC; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and MDI is 1:1.25:0.95.
[0086] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 90 parts of PP, 10 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and the flame retardant, high-strength and tough modified CNC are mixed in a mixer at 200°C and 50 rpm to achieve torque balance, and then DCP is added and mixed to achieve torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0087] Example 9
[0088] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0089] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0090] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0091] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 50° C. for 32 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 18 hours to obtain hydrophobic CNC;
[0092] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 140°C, start stirring, and add 2,2,4-trimethylhexane diisocyanate (TMDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 2 hours. After the reaction is completed, flame retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and TMDI is 1:1.25:0.95.
[0093] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 90 parts of PP, 10 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 180°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0094] Example 10
[0095] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0096] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0097] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0098] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 50° C. for 32 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 18 hours to obtain hydrophobic CNC;
[0099] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 145°C, start stirring, and add toluene diisocyanate (TDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 3 hours. After the reaction is completed, flame-retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and TDI is 1:1.25:0.95.
[0100] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 90 parts of PP, 10 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 180°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0101] Embodiment 11
[0102] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0103] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0104] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0105] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 60° C. for 24 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 24 hours to obtain hydrophobic CNC;
[0106] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 140°C, start stirring, and add isophorone diisocyanate (IPDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 4 hours. After the reaction is completed, flame-retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and IPDI is 1:1.25:0.95.
[0107] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 80 parts of PP, 20 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 190°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0108] Example 12
[0109] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0110] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0111] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0112] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 75° C. for 28 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 12 hours to obtain hydrophobic CNC;
[0113] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 145°C, start stirring, and add 4,4'-dicyclohexylmethane diisocyanate (HMDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 2 hours. After the reaction is completed, flame-retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and HMDI is 1:1.25:0.95.
[0114] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 80 parts of PP, 20 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 200°C and 50 rpm to achieve torque balance, and then DCP is added and mixed to achieve torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0115] Example 13
[0116] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0117] (1) adding 1 g of γ-aminopropyltriethoxysilane to 25 ml of water with stirring, adjusting the pH value to 8-10 and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0118] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0119] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 75° C. for 28 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 12 hours to obtain hydrophobic CNC;
[0120] (2) Add the above-mentioned hydrophobic CNC and propylene glycol-Α,Α'-diallyl ether into a reaction bottle, heat to 140°C, start stirring, and add hexamethylene diisocyanate (HDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 3 hours. After the reaction is completed, flame-retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, propylene glycol-Α,Α'-diallyl ether, and HDI is 1:1.25:0.95.
[0121] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 80 parts of PP, 20 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 200°C and 50 rpm to achieve torque balance, and then DCP is added and mixed to achieve torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0122] Embodiment 14
[0123] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0124] (1) adding 1 g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane to 25 ml of water with stirring, adjusting the pH value to 8-10 and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0125] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0126] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 75° C. for 32 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 18 hours to obtain hydrophobic CNC;
[0127] (2) The above-mentioned hydrophobic CNC and 2,2-bis(allyloxymethyl)-1-butanol are added to a reaction bottle, the temperature is raised to 145°C, stirring is started, and hexamethylene diisocyanate (HDI) is added dropwise for heating reaction. After the addition is completed, the reaction is continued for 2 hours. The reaction is completed to obtain flame-retardant and high-strength modified CNC; wherein the mass ratio of hydrophobic CNC, 2,2-bis(allyloxymethyl)-1-butanol, and HDI is 1:1.25:0.95.
[0128] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 80 parts of PP, 20 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 180°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0129] Embodiment 15
[0130] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0131] (1) adding 1 g of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane to 25 ml of water with stirring, adjusting the pH value to 8-10 and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0132] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0133] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 60° C. for 24 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 24 hours to obtain hydrophobic CNC;
[0134] (2) Add the above-mentioned hydrophobic CNC and 2,2-bis(allyloxymethyl)-1-butanol into a reaction bottle, heat to 145°C, start stirring, and add hexamethylene diisocyanate (HDI) dropwise for heating reaction. After the addition is completed, continue the reaction for 4 hours. After the reaction is completed, flame-retardant and high-strength modified CNC is obtained; wherein the mass ratio of hydrophobic CNC, 2,2-bis(allyloxymethyl)-1-butanol, and HDI is 1:1.25:0.95.
[0135] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 80 parts of PP, 20 parts of the flame retardant, high-strength and tough modified CNC, and 0.2 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 190°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0136] Example 16
[0137] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0138] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0139] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0140] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 60° C. for 24 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 24 hours to obtain hydrophobic CNC;
[0141] (2) The above-mentioned hydrophobic CNC and 2,2-bis(allyloxymethyl)-1-butanol are added to a reaction bottle, the temperature is raised to 140°C, stirring is started, and hexamethylene diisocyanate (HDI) is added dropwise for heating reaction. After the addition is completed, the reaction is continued for 4 hours. The reaction is completed to obtain flame-retardant and high-strength modified CNC; wherein the mass ratio of hydrophobic CNC, 2,2-bis(allyloxymethyl)-1-butanol, and HDI is 1:1.25:0.95.
[0142] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 80 parts of PP, 20 parts of the flame retardant, high-strength and tough modified CNC, and 0.4 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 190°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0143] Embodiment 17
[0144] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0145] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0146] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0147] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 60° C. for 24 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 24 hours to obtain hydrophobic CNC;
[0148] (2) The above-mentioned hydrophobic CNC and 2,2-bis(allyloxymethyl)-1-butanol are added to a reaction bottle, the temperature is raised to 145°C, stirring is started, and hexamethylene diisocyanate (HDI) is added dropwise for heating reaction. After the addition is completed, the reaction is continued for 2 hours. The reaction is completed to obtain flame-retardant and high-strength modified CNC; wherein the mass ratio of hydrophobic CNC, 2,2-bis(allyloxymethyl)-1-butanol, and HDI is 1:1.25:0.95.
[0149] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 95 parts of PP, 5 parts of the flame retardant, high-strength and tough modified CNC, and 0.3 parts of DCP; the preparation method is: PP and flame retardant, high-strength and tough modified CNC are mixed in a mixer at 190°C and 50 rpm to achieve torque balance, and then DCP is added to continue mixing until torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0150] Embodiment 18
[0151] The preparation method of flame-retardant high-strength and tough modified nanocellulose comprises the following steps:
[0152] (1) adding 1 g of γ-aminopropyltrimethoxysilane to 25 ml of water, stirring, adjusting the pH value to 8-10, and hydrolyzing under alkaline conditions to obtain a hydrolyzate;
[0153] Add 1 g of CNC to 15 ml of ethanol and disperse evenly to obtain a CNC-ethanol dispersion;
[0154] The hydrolyzate is added to the CNC-ethanol dispersion to carry out grafting reaction at 75° C. for 28 hours, and after cooling, it is washed with alcohol and water for multiple times, and then vacuum dried at 55° C. for 12 hours to obtain hydrophobic CNC;
[0155] (2) The above-mentioned hydrophobic CNC and 2,2-bis(allyloxymethyl)-1-butanol are added to a reaction bottle, the temperature is raised to 145°C, stirring is started, and hexamethylene diisocyanate (HDI) is added dropwise for heating reaction. After the addition is completed, the reaction is continued for 3 hours. The reaction is completed to obtain flame-retardant and high-strength modified CNC; wherein the mass ratio of hydrophobic CNC, 2,2-bis(allyloxymethyl)-1-butanol, and HDI is 1:1.25:0.95.
[0156] The flame retardant, strong and tough balanced polypropylene composite material comprises, by weight: 97.5 parts of PP, 2.5 parts of the flame retardant, high-strength and tough modified CNC, and 0.3 parts of DCP; the preparation method is: PP and the flame retardant, high-strength and tough modified CNC are mixed in a mixer at 200°C and 50 rpm to achieve torque balance, and then DCP is added and mixed to achieve torque balance, and the flame retardant, strong and tough balanced polypropylene composite material is obtained after granulation. After injection molding, it is tested.
[0157] Comparative Example 1
[0158] This comparative example is PP raw material pellets, which are tested after injection molding.
[0159] Comparative Example 2
[0160] The material of this comparative example was prepared as follows: 100 parts by weight of dried PP pellets were added to a mixer for melt blending at a mixer temperature of 190°C and a mixer speed of 50 rpm until the blending torque was balanced; then 0.2 parts by weight of DCP was added, and melt reactive blending was continued until the torque was balanced, and polypropylene material was obtained after granulation. After injection molding, it was tested.
[0161] Comparative Example 3
[0162] The material of this comparative example was prepared as follows: 90 parts by weight of dried PP particles and 10 parts by weight of hydrophobic CNC (using the hydrophobic CNC in Example 11) were added to a mixer for melt blending at a mixer temperature of 190°C and a rotation speed of 50 rpm until the blending torque was balanced; then 0.2 parts by weight of DCP was added, and melt reactive blending was continued until the torque was balanced, and polypropylene material was obtained after granulation. After injection molding, it was tested.
[0163] Comparative Example 4
[0164] The materials of this comparative example were prepared according to the following steps: using the mass ratio of hydrophobic CNC, glycerol-Α,Α'-diallyl ether, and IPDI in Example 11, the three were mixed uniformly to obtain a premixed material (without reaction);
[0165] 80 parts by weight of dried PP particles and 20 parts by weight of the above premixed materials were added to a mixer for melt blending at a mixer temperature of 190°C and a rotation speed of 50 rpm until the blending torque was balanced; then 0.2 parts by weight of DCP was added, and melt reactive blending was continued until the torque was balanced, and polypropylene material was obtained after granulation. After injection molding, it was tested. The above examples and comparative examples are shown in Table 1.
[0166] Table 1 Examples and Comparative Examples
[0167]
[0168] The performance of the composite materials of the above embodiments and comparative examples was tested, and the specific results are shown in Table 2.
[0169] Table 2 Composite material properties of the embodiments and comparative examples
[0170]
[0171]
[0172] From the formula in Table 1 and the data in Table 2, it can be seen that by modifying the nanocellulose to be flame retardant and hydrophobic and then blending it with PP, it is helpful to improve the strength, toughness, heat resistance and flame retardancy of the composite material. When the mass ratio of hydrophobic nanocellulose, hydroxyl-containing diallyl ether and diisocyanate is 1:1.25:0.95, the flame retardant high-strength and tough modified CNC is obtained by reaction, and after it is compounded with polypropylene (the flame retardant high-strength and tough modified CNC is added according to 20 parts by weight), the tensile strength of the composite material can reach more than 34MPa, and the maximum can reach 37.1MPa; the flexural strength of the composite material can reach more than 38MPa, and the maximum can reach 43.2MPa; the impact strength of the composite material can reach 19kJ / m 2 Above, the maximum can reach 23kJ / m 2The heat deformation temperature of the composite material can reach above 70°C, and the maximum can reach 78°C. The contact angle of the composite material can reach a maximum of 111°. The vertical combustion of the composite material can reach at least V-1 flame retardant level, and the oxygen index can reach a maximum of 32.4%.
[0173] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing flame-retardant, high-strength and tough modified nanocellulose, characterized in that: The steps include: (1) grafting a hydrophobic agent onto the surface of nanocellulose to obtain hydrophobic nanocellulose, wherein the hydrophobic agent is a silane having at least one amino functional group; (2) The hydrophobic nanocellulose and the hydroxyl-containing diallyl ether compound are subjected to a heating reaction under the action of diisocyanate to obtain flame-retardant and high-strength modified nanocellulose.
2. The method for preparing the flame-retardant, high-strength and tough modified nanocellulose according to claim 1, characterized in that: The nanocellulose includes one or more of cellulose nanocrystals, cellulose microcrystals, cellulose nanofibers, and bacterial nanocellulose; The silane having at least one amino functional group is selected from one or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane; The hydroxyl-containing diallyl ether compound is glycerol-Α,Α'-diallyl ether and / or 2,2-bis(allyloxymethyl)-1-butanol; The diisocyanate is selected from one or more of hexamethylene diisocyanate, diphenylmethane diisocyanate, 2,2,4-trimethylhexane diisocyanate, toluene diisocyanate, isophorone diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.
3. The method for preparing the flame-retardant, high-strength and tough modified nanocellulose according to claim 1, characterized in that: The mass ratio of the hydrophobic nanocellulose, the hydroxyl-containing diallyl ether compound, and the diisocyanate is 1:(1.1-1.25):(0.85-0.95).
4. The method for preparing the flame-retardant, high-strength and tough modified nanocellulose according to claim 1, characterized in that: The temperature of the heating reaction in step (2) is 140-145° C., and the reaction is continued for 2-4 hours after the diisocyanate is added.
5. The method for preparing the flame-retardant, high-strength and tough modified nanocellulose according to claim 1, characterized in that: The process of grafting the hydrophobic agent on the surface of the nanocellulose in step (1) is: hydrolyzing the hydrophobic agent under alkaline conditions to obtain a hydrolyzate, adding the hydrolyzate to an ethanol dispersion of nanocellulose to carry out a grafting reaction at 50-75° C. for 24-32 hours, cooling, washing with alcohol and water for multiple times, and then drying to obtain the hydrophobic nanocellulose.
6. The method for preparing the flame-retardant, high-strength and tough modified nanocellulose according to claim 5, characterized in that: The mass concentration of the hydrophobic agent in the hydrolyzate is 3-5%, and the pH of the alkaline condition is 8-10; the mass concentration of nanocellulose in the nanocellulose ethanol dispersion is 5-10%; and the mass ratio of the nanocellulose to the hydrophobic agent is 1:(1-5).
7. The flame-retardant and high-strength modified nanocellulose is obtained according to the preparation method according to any one of claims 1 to 6.
8. Flame retardant and tough balanced polyolefin, characterized in that: The invention comprises the following components in parts by weight: 80-100 parts of polyolefin, at least 1 part of flame-retardant and high-strength modified nanocellulose obtained by the preparation method according to any one of claims 1 to 6, and 0.2-0.4 parts of an organic peroxide initiator.
9. The flame retardant and strong-tough balanced polyolefin according to claim 8, characterized in that: The polyolefin is one or more of PE, PP, PB, TPX, and polyolefin thermoplastic elastomers; the organic peroxide initiator includes one or more of BPO, DCP, TMCH, DHBP, BIPB, TBPB, TBCP, DBPH, and DTBP.
10. The flame retardant and strong-tough balanced polyolefin according to claim 8, characterized in that: The preparation of the flame-retardant, strong and tough balanced polyolefin comprises the following steps: according to the formula, other materials except the organic peroxide initiator are melt-reactively blended at at least 150° C. until torque balance is achieved, then the organic peroxide initiator is added and melt-reactively blended until torque balance is achieved, and the flame-retardant, strong and tough balanced polyolefin is obtained after granulation.
Citation Information
Patent Citations
Biodegradable tough composite material and preparation method thereof
CN115433442A
Nanocellulose composite filler as well as preparation method and application thereof
CN115636986A
External toughening agent for phenol formaldehyde resin as well as preparation method and application of external toughening agent
CN104804101A
Polylactic acid / nanocellulose halogen-free flame-retardant composite material
CN113321910A